Comparison of cataract patients with regular corneal astigmatism after implantation of extended range-of-vision and bifocal toric intraocular lenses - Li, Zhuoya; Guo, Rong; Hu, Xiaomin; Yang, Xinyue; Wen, Ziyuan; Lin, Yi; Zhang, Hui (Frontiers in Medicine, 2023)
Purpose: To compare the postoperative visual acuity and visual quality between extended-range-of-vision and multifocal toric intraocular lens (IOL) implantation in cataract patients with regular corneal astigmatism. Setting: Eye Center of the Second Hospital of Jilin University, Changchun, China Design: Retrospective and single-center Study. Methods: Fifty-nine patients with regular corneal astigmatism (range, 1.0 to 1.5 D) who underwent cataract phacoemulsification combined with IOL implantation at our hospital between January 2021 and January 2022 were selected. The patients were divided into two groups: 33 patients with Tecnis Symphony (ZXR00) in the ZXR group and 26 patients with Tecnis ZMT in the ZMT group. Parameters of postoperative visual acuity and visual quality were compared three months after the operation. Results: The 3-month postoperative follow-up showed that both groups had good corrected distance vision. The ZMT group had better uncorrected distance visual acuity and near visual acuity. The ZXR group showed better-uncorrected intermediate visual acuity and visual continuity. Postoperative astigmatism in the ZMT group was significantly lower than that in the preoperative astigmatism group. The ZMT group had a lower tHO, higher MTF value, and higher VF-14 score. However, the ZXR group exhibited slighter halo and glare phenomena. Conclusions: Both groups produced good corrected distance vision, but had differing effects on other visual parameters. Therefore, personalized treatment plans for patients should be made, including choosing between ZXR00 IOL that contains astigmatism, or ZMT IOL that corrects astigmatism.